Hyperreality in the Flexing Culture of Mass Media Communication - Kusuma, Irawinne Rizki Wahyu (Jurnal Multidisiplin Sahombu, 2025)
This study examines the phenomenon of hyperreality in flexing culture in mass communication, particularly through social media. Flexing culture, as the behavior of excessively flaunting lifestyle and luxury on digital platforms, represents hyperreality in which images and simulations replace factual reality. This study aims to understand how mass media shapes public perception through the construction of manipulative virtual images, as well as its impact on individual psychology and social structures. The research method uses a qualitative approach with content analysis on popular social media and in-depth interviews with flexing actors and their audiences. This study integrates Jean Baudrillard's theory of hyperreality with contemporary studies of flexing behavior on social media platforms as an arena of modern mass communication. The results show that hyperreality in flexing culture creates social pressure and the need for validation that impacts consumer behavior and social identity in the digital era. The implications of this research open a critical discourse on the role of mass media in producing new, simulative social realities.